The modern approach to mantle cell lymphoma. (12th June 2019) - Rule, Simon
Abstract: Mantle Cell Lymphoma is a rare and generally aggressive form of non Hodgkin lymphoma. Our understanding of the pathophysiology of this disease is improving and whilst risk factors are understood, treatments are not yet tailored towards these. The treatment algorithm in the front line is well established for older and younger patients and observation is the norm for a subset of patients although these are not well characterised as yet. In the relapse setting the role of novel agents, especially the BTK inhibitors is becoming established and combination approaches look promising. Trials are beginning to challenge the role of chemotherapy against the novel agents especially as part of front line therapy. As a consequence it is likely we will see a paradigm shift in the management of this disease in the next few years.